PICES Press, Vol. 20, No. 1, Winter 2012 (North Pacific Marine Science Organization (PICES), 2012)
•2011 PICES Science: A Note from the Science Board Chairman (pp. 1-6) •2011 PICES Awards (pp. 7-9) •Beyond the Terrible Disaster of the Great East Japan Earthquake (pp. 10-12) •A New Era of PICES-ICES Scientific Cooperation (p. 13) •New PICES Jellyfish Working Group Formed (pp. 14-15) •PICES Working Group on North Pacific Climate Variability (pp. 16-18) •Final U.S. GLOBEC Symposium and Celebration (pp. 19-25) •2011 PICES Rapid Assessment Survey (pp. 26-29) •Introduction to Rapid Assessment Survey Methodologies for Detecting Non-indigenous Marine Species (pp. 30-31) •The 7th International Conference on Marine Bioinvasions (pp. 32-33) •NOWPAP/PICES/WESTPAC Training Course on Remote Sensing Data Analysis (pp. 34-36) •PICES-2011 Workshop on “Trends in Marine Contaminants and their Effects in a Changing Ocean” (pp. 37-39) •The State of the Western North Pacific in the First Half of 2011 (pp. 40-42) •Yeosu Symposium theme sessions (p. 42) •The Bering Sea: Current Status and Recent Events (pp. 43-44) •News of the Northeast Pacific Ocean (pp. 45-47) •Recent and Upcoming PICES Publications (p. 47) •New leadership for the PICES Fishery Science Committee (p. 48)